Measurement of dijet production with a leading proton in proton-proton collisions at √s=8 Tev with the CMS and TOTEM detectors at the LHC - Huertas Guativa, Lina Milena (2017)
A study of dijet production associated with a leading proton is presented. The analysis is based on a common data set collected simultaneously with the CMS and TOTEM experiments at the LHC with proton-proton collisions at √s=8 Tev during a dedicated run with β^* = 90 m, at low instantaneous luminosity. The data correspond to an integrated luminosity of 37:5 nb-1. The analysis presents the measurements of the dijet production cross section, as a function of ε, the proton fractional momentum loss, and as a function of t, the 4-momentum transfer squared at the proton vertex. The dijet cross section in the kinematic region defined by ε < 0:1, 0:03 < t < 1 Ge√^2, ε < 0, 1, for jets with transverse momentum pT > 40 GeV, and pseudorapidity n < 4:4, was measured to be [...]. The suppression factor of the cross section with respect to the prediction from the diffractive PDFs measured at HERA is also presented. The ratio of the single-diffractive to inclusive dijet yields is presented as a function of x, the momentum fraction of the parton initiating the hard scattering. The ratio in the kinematic region defined above, for x values in the range [...] was measured as [...] .